Traditional Leaders' Communication Strategies in Fostering Harmony Through the Selamat Kampong Tradition in Belitung - Nurul Aulia Rahmani; Iman Sumarlan (Publikasi Indonesia, 2025)
Selamat kampong is a tradition or custom that has been passed down from generation to generation and is carried out in every village in Belitung. Selamat kampong is not only an annual routine tradition in Aik Rayak Village, Belitung Regency, but the implementation of this event contains several aspects such as traditions, approaches, and communication strategies. This study aims to find out how the communication strategy of traditional leaders creates a sense of peace in the tradition of surviving the village in Aik Rayak Village, Tanjungpandan District, Belitung Regency. This study uses a qualitative method with a descriptive approach. The results of the study show that traditional leaders use persuasive communication with 3 persuasive communication strategies: (1) Psychodynamic strategies, involving the community and the younger generation, and evoking emotions through joint prayer to foster a sense of responsibility and increase togetherness. (2) Sociocultural strategy, namely collaborating with LAM (Malay Customary Institution) and implementing Islamic culture to create a sense of peace. (3) The meaning construction strategy, which is the provision of knowledge on understanding traditional values and cultural identity to strengthen solidarity between village communities. This study concludes that the communication strategy of traditional leaders plays an important role in maintaining cultural traditions and stability in Aik Rayak Village.